State Dependence in Welfare Benefits in a Non-Welfare Context - Sinem H. Ayhan; Selin Pelek (Institute for the Study of Labor (IZA), 2015)
This study contributes to the ongoing debate about welfare dependency centered on the western societies through an empirical analysis, within the context of a developing country. It examines state dependence in social assistance benefit receipt using longitudinal data from Turkey, where benefit receipt and persistence rates have witnessed a significant increase since the last decade. Identification is achieved by dynamic random effects probit models, controlling for unobserved heterogeneity and endogenous initial conditions. Particularly, Wooldridge's (2005) estimator and its extensions are applied for achieving consistent and correct estimates of state dependence. In order to check for sensitivity, the results are compared with the results from Heckman's (1981) reduced form approach. Both estimators enable us to deal with the potential bias due to the short panel length. It is found that the benefit receipt of the last year increases the likelihood of benefit receipt in the current year by 17 to 22 percentage points. This evidence suggests that state dependence in social assistance might also be a relevant phenomenon for developing countries.
Keywords: I30; I38; J18; C23; 330; social assistance benefits; state dependence; endogenous initial conditions; dynamic random effects models